Urban wastewater treatment by Tetraselmis sp CTP4 (Chlorophyta) - Schulze, Peter S.C. (2019)
The ability of a recent isolate, Tetraselmis sp. CTP4, for nutrient removal from sewage effluents before and after the nitrification process under batch and continuous cultivation was studied. Biomass productivities in both wastewaters were similar under continuous conditions ( 0.343 +/- 0.053 g L-1 d(-1)) and nutrient uptake rates were maximal 31.4 +/- 0.4 mg N L-1 d(-1) and 6.66 +/- 1.57 mg P-PO43 L- 1 d(-1) in WW before nitrification when cultivated in batch. Among batch treatments, cellular protein, carbohydrate and lipid levels shifted with aging cultures from 71.7 +/- 6.3 to 29.2 +/- 1.2%, 17.4 +/- 7.2 to 57.2 +/- 3.9% and 10.9 +/- 1.7 to 13.7 +/- 4.7%, respectively. In contrast, CTP4 cultivated continuously in Algal medium (control) showed lower biomass productivities ( 0.282 g VSS L-1 d(-1)) although improved lipid content (up to 20% lipids) in batch cultivation. Overall, Tetraselmis sp. CTP4 is promising for WW treatment as a replacement of the costly nitrification process, fixating more nutrients and providing a protein and carbohydrate-rich biomass as by-product. (C) 2016 Elsevier Ltd. All rights reserved.